Visual assessment of the impact of agricultural management practices on soil quality. (30th April 2020) - Alaoui, Abdallah; Barão, Lúcia; Ferreira, Carla S. S.; Schwilch, Gudrun; Basch, Gottlieb; Garcia‐Orenes, Fuensanta; Morugan, Alicia; Mataix‐Solera, Jorge; Kosmas, Costas; Glavan, Matjaž; Szabó, Brigitta; Hermann, Tamás; et al.
Abstract: The intensification of agricultural practices to increase food and feed outputs is a pressing challenge causing deterioration of soil quality and soil functions. Such a challenge demands provision of empirical evidence to provide context‐sensitive guidance on agricultural management practices (AMPs) that may enhance soil quality. The objectives of this study are to identify the most promising AMPs (and their combinations) applied by farmers with the most positive effects on soil quality and to evaluate the sensitivity of the soil quality indicators to the applied AMPs. The effect of selected AMPs on soil quality was assessed using a visual soil assessment tool in a total of 138 pairs of plots spread across 14 study site areas in Europe and China covering representative pedo‐climatic zones. The inventory and scoring of soil quality were conducted together with landowners. Results show that 104 pairs show a positive effect of AMPs on soil quality. Higher effects of the AMPs were observed in lower fertile soils (i.e., Podzols and Calcisols) as opposed to higher fertile soils (i.e., Luvisols and Fluvisols). For the single use applications, the AMPs with positive effects were crop rotation; manuring, composting, and no‐tillage; followed by organic agriculture and residue maintenance. Cluster analysis showed that the most promising combinations of AMPs with the most positive effects on soil quality are composed of crop rotation, mulching, and min‐till. The agreement between scientific skills and empirical knowledge in the field identified by the farmers confirm our findings and ensures their applicability.